Factors Affecting Birth of Low Birth Weight Babies of Pregnant Women Attending Antenatal Care in Wang Wiset Hospital, Trang Province - Phayuhasenarak, Somkiert; Purinthapibal, Sopit (Journal of Health Science of Thailand, 2020)
The objective of this study was to identify the incidence and the factors affecting low birth weight babiesin order to control and solve the problem of low birth weight babies and to be used in planning for further improvement of maternal and child health. Data were collected from 422 pregnant women attending the antenatal clinic in Wang Wiset Hospital, Trang Province and giving birth in 2016-2018. The studied factors including preliminary data of mothers, including age; body weight before pregnancy; education; occupation; religion; marital status; history of abortion, childbirth and congenital disease; pregnancy care factors, such as gestational age at the first antenatal care; weight gain during pregnancy; number of antenatal care visits; red blood cell concentration during antenatal care; prenatal red blood cell concentration; complications during pregnancy; gestational age, and the dependent variables include the weight of the newborn. The results showed that 19.3% of pregnant women were under 20 years old, mostly secondary education, had a job, and Buddhist religion. Among them, 97.8% lived with their husbands, the first childbirth was 36.3%, and 10.8% had a history of abortion. The most common chronic disease was thyrotoxicosis (0.8%), followed by anemia (0.4%). The gestational age at the first antenatal care visit lower 12 weeks (39.0%), pre-gestational body weight less than 45 kilograms (9.6%), having 4 and higher ANC visits (87.4%), prenatal hemoglobin concentration less than 33 percent (42.2%). There was no complication during pregnany. Low birth weight (under 2,500 grams) was observed in 9.0% of the newborns. Factors significantly associated with low birth weight (p<0.05) were: weight gain during pregnancy less than 10 kilograms (p=0.001, Odds ratio = 23.603, 95%CI=3.644-45.578); the number of visits for prenatal care (p=0.001, Odds ratio=7.923, 95%CI=2.916-21.529), gestational age in pregnant women (p=0.001, Odds ratio=7.870, 95%CI=2.681-23.105), Therefore, prevention of low birth weight would require increasing focus on preparing the mother before pregnancy in order to increase weight gain of not less than 10 kilograms, increase the number of ANC visits (more than 4), and to provide care and closely monitor pregnant women with gestational age 37 weeks and beyond.